2013
DOI: 10.1159/000355554
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Psychotic-Like Experiences Are a Poor Estimate of Clinician-Rated Attenuated and Frank Delusions and Hallucinations

Abstract: Background: One reason for the decision to delay the introduction of an Attenuated Psychosis Syndrome in the main text of the fifth edition of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders was the concern that attenuated psychotic symptoms (APS) might in fact be common features in adolescents and young adults from the general population of no psychopathological significance in themselves. This concern was based on reports of high prevalence rates of psychotic-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 38 publications
4
54
0
1
Order By: Relevance
“…The sample size in this study was comparable to other screening evaluation studies in clinical samples (Kline and Schiffman 2014;Schultze-Lutter et al 2014) and was also sufficient to detect a clinically useful κ against the null hypothesis of no agreement between assessment modes with a power of 90% (Sim and Wright 2005). A clear disadvantage of the current study was, however, shown in the limited content validity of the FCQ as a result of the incomplete overlap between the BS included in FCQ and SPI-A/SPI-CY.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The sample size in this study was comparable to other screening evaluation studies in clinical samples (Kline and Schiffman 2014;Schultze-Lutter et al 2014) and was also sufficient to detect a clinically useful κ against the null hypothesis of no agreement between assessment modes with a power of 90% (Sim and Wright 2005). A clear disadvantage of the current study was, however, shown in the limited content validity of the FCQ as a result of the incomplete overlap between the BS included in FCQ and SPI-A/SPI-CY.…”
Section: Discussionsupporting
confidence: 61%
“…Although BS rely less on interviewer appraisal than attenuated positive symptoms, the FCQ's concurrent validity is only as good as that reported among self-report assessments of attenuated positive symptoms when a cut-off is chosen that optimises both sensitivity and specificity (Kline and Schiffman 2014). Thus, in line with reports on differences between self-report and clinical assessments of BS and attenuated positive symptoms (Granö et al 2011;Maß et al 1997;Ochoa et al 2008;Schultze-Lutter et al 2014;Yung et al 2009), we found a significant overestimation of clinician-rated BS by self-rated BS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of an asthmamonitoring app reported that, while over 49,000 people downloaded the study's app, only 175 (0.35%) were actively engaged with it at six months 5 . A successful study of an app for alcohol use disorder 6 reported less success when later deploying without broad incentives 7 .…”
Section: Bridging the Dichotomy Of Actual Versus Aspirational Digitalmentioning
confidence: 99%
“…Until recently, epidemiological studies have mainly used self-rating questionnaires or standardized lay-person interviews for the assessment of "psychotic-like experiences" (PLEs) 4,5 , that are usually equaled to (attenuated) psychotic symptoms by critics 3 . Yet, questionnaire studies significantly overestimate the prevalence of PLEs already in comparison to lay-person interview studies 5 , and even more in comparison to clinician-based evaluations of APS using psychosis-risk assessment instruments 6 .…”
mentioning
confidence: 99%
“…Investigaciones realizadas con éste y otros cuestionarios autoadministrados, demuestran que tienden a sobrevalorar los síntomas en las poblaciones estudiadas (89)(90)(91).…”
Section: Rev Neuropsiquiatr 80 (1) 2017unclassified